HUBUNGAN ANTARA MULTIPLE INTELLIGENCE DENGAN PRESTASI BELAJAR SISWA KELAS XI DI SMA NEGERI 10 MALANG - Andreas Teguh Raharjo (University of Merdeka Malang, 2010)
This study was to determine the relationship between Multiple Intelligence with Class XI student achievement in SMAN 10 Malang. The sample is 105 student, with Proportional Random Sampling technique. The instrument for collecting data is method of scale. To determine relationship of the variable X (Linguistic Intelligence, Logic-Mathematic Intelligence, Bodily-Kinesthetic Intelligence, naturalistic Intelligence, Musical Intelligence, Interpersonal Intelligence) to variable Y (B.Indonesia, B.Inggris, Mathematics, Physical Education and Health , Biology, Art and Culture, Citizenship) used multiple correlation. Linguistic analysis of test-B.Indonesia obtained r = -0.065 with ? = 0.516; Linguistic-B.Inggris r = -0.049 with ? = 0.627; LogicMathematic-Mathematics r = 0.014 with ? = 0.879; Kinethetic-Physical r = -0.011 with ? = 0.905; naturalistic-r = -0.191 Biology with r2 = 0.036 and ? = 0.048; Musical Art-r = 0.062 with ? = 0.536; Interpersonal, Citizenship r = 0.116 with ? = 0.236. Linguistic Intelligence is not correlate with the subjects of English Language and Indonesia language, Logic-Mathematic Intelligence is not correlate with the subjects of Mathematics, Bodily-Kinesthetic Intelligence is not correlate with the subjects of Physical Education and Health, Musical Intelligence is not correlate with the subjects of Arts and Education Culture, Interpersonal Intelligence is not correlate with the subjects of Citizenship, while naturalistic Intelligence correlate with the subjects of Biology with a negative correlation. This means that the higher score of naturalistic Intelligence so the achievement scores of Biology to be lower. Naturalistic intelligence contributed only 3.6% to the Biology achievement score tets. Keywords : Multiple Intelligence, Academic Achievement